Structure–function relationship in early diabetic retinopathy: a spatial correlation analysis with OCT and microperimetry - Montesano, G; Gervasoni, A; Ferri, P; Allegrini, D; Migliavacca, L; De Cillà, S; Rossetti, L (Eye (London), 2017)
Purpose To study the correlation of the local ganglion cell layer—inner plexiform layer (GCL-IPL) thickness with corresponding retinal sensitivity as studied with microperimetry in patients with Type 2 diabetes and no signs of diabetic retinopathy. Patients and methods We analyzed 35 healthy subjects (68 eyes) and 26 Type 2 diabetic patients (48 eyes) with no signs of diabetic retinopathy. We tested best corrected visual acuity (BCVA), monocular and binocular constrast sensitivity (CS, Pelli – Robson chart) and retinal sensitivity with microperimetry, and acquired dense macular SD-OCT scans. We then studied the correlation between local GCL-IPL thickness and local sensitivity. Results Mean BCVA was 1.09 (±1.03) decimals in diabetic subjects and 1.02 (±0.15) decimals in healthy subjects. Only binocular CS was significantly higher in healthy subjects (1.18±0.42 for healthy subjects, 1.62±0.63 for diabetic subjects). In both local and global analysis we observed higher GCL-IPL thickness and higher sensitivity in normal compared with diabetic subjects, but no difference reached significance ( p <0.05). Using a mixed multivariate linear model, we found a significant correlation between retinal sensitivity and the correspondent GCL-IPL thickness in diabetic subjects (0.022±0.006 dB/ μ m, p =0.0007) but not in healthy subjects (−0.002±0.006 dB/ μ m, p =0.77). Conclusion despite close similarities between the two groups, we found a significant difference in the structure–function relationship in diabetic subjects without diabetic retinopathy, suggesting that diabetes might act as an additional effect in the normal deterioration of the visual function related to the inner retina.